Ectoparásitos y endoparásitos presentes en Pygocentrus nattereri (Kner, 1858) (characiformes, serrasalmidae) "piraña roja" comercializados en el mercado Belén, Iquitos-Perú - Castro Saavedra, Paulita Beatriz (2022)
The present investigation of this research was to determine the ectoparasites and endoparasites present in Pygocentrus nattereri "red piranha" marketed in the Belén Market, Iquitos-Perú during the dry season. Fifty specimens were acquired with an average weight and length of 216.5 g and 17.15 cm, and were examined at the laboratory of Parasitology and Aquaculture Health of the Research Institute of the Peruvian Amazon. The parasites present in the gills, nostrils, muscle and internal organs were analyzed, described and identified; being fixed and preserved according to the methodology already proposed according to the parasite group. A total of 1907 parasites were collected and identified (1828 ectoparasites and 79 endoparasites), belonging to 6 taxonomic groups: Monogenoidea; Branchiura, Copepoda, Nematoda; Pentastomida and Digenea. At the species level, a total of 25 species of parasites were recorded and 5 only at the genus level between ectoparasites and endoparasites. The monogenoids was the group with 100% prevalence. At the species level, the most prevalent with 78% was Anacanthorus reginae. Anacanthorus thatcheri was the species with the highest average abundance of infection with 11.64 and with a dominance percentage greater than 30%. Finally, Mymarothecium viatorum obtained a mean infection intensity (IMI) of 26. The ecological indices indicate a medium richness and diversity in relation to the number of species identified. In the zoonotic parasites, 05 genera with zoonotic potential were recorded in the present study (Anisakis, Contracaecum, Pseudoterranova, Sebekia and Clinostomum), divided into 03 taxonomic groups (Nematoda, Pentastómida and Digenea). Clinostomum marginatum was only identified to the species level. Zoonotic parasites were located in the intestines and in the musculature. In the correlations between length and weight and the variables (Monogenoid, ectoparasites and endoparasites) the values obtained show us that there is no correlation between the variables studied.